Can the Czech road tax be considered a tax on externalities? - Petr David (European Financial and Accounting Journal, 2019)
The transport sector is one of the important components of economic systems. Besides positive effects, it is also a source of external costs transferred to other entities. Through the evaluation of current settings of the tax base and parameters of the road tax rate progressivity it was ascertained that this tax fails to directly or indirectly reflect the external costs of transport. It is through a relatively simple adjustment of the existing road tax rates that indirect reflection of certain items of the road transport external costs may be achieved. Firstly, changes must be made in the definition of the road tax base so as to contain emissions or other parameters of externalities; subsequently, the direct reflection of the road transport external costs in the tax may be achieved.
Keywords: H21; H23; 650; Czech Republic; Externality; Road tax; Tax rate